Microbiology - Baker, Simon (Garland Science, 2011)
BIOS Instant Notes in Microbiology, Fourth Edition, is the perfect text for undergraduates looking for a concise introduction to the subject, or a study guide to use before examinations. Each topic begins with a summary of essential facts-an ideal revision checklist-followed by a description of the subject that focuses on core information, with clear, simple diagrams that are easy for students to understand and recall in essays and exams.